Pentingnya Pemahaman Akuntansi Sederhana Sebagai Solusi Untuk Menyusun Laporan Keuangan (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2020)
Financial reports serve as a tool for analyzing financial performance that can provide information about business finances so that they can be used as a basis for making decisions. The object of this research is UD Rian Arianto Farm, which is engaged in the farming and trade of native chickens in Bogor. The purpose of this research is to provide knowledge to Partners about the importance of compiling financial reports to carry out a business activity either manually or computerized which can make it easier for Partners to make financial reports based on SAK EMKM (Financial Accounting Standards for Micro, Small and Medium Entities). The writer collected data by means of interviews and documentation.